Association between low vitamin D levels and key characteristics of COVID-19 patients: a retrospective cross-sectional study - Mohammad Sallehuddin, Hakimah; Wan Ghazali, Wan Syamimee; Shahril, Shuhaila; Bidin, Jasrina; Kah, Keng Wong; Bidin, Mohammad Zulkarnain (Universiti Putra Malaysia, 2024)
Introduction: Vitamin D deficiency associated with COVID-19 patients has recently garnered interest. This is likely due to the elderly population who are most commonly affected by COVID-19. In this study, we investigated the association of vitamin D levels with the clinico-demographical and laboratory characteristics of COVID-19 patients. Methods: We recruited 77 COVID-19 patients who were admitted to Hospital Pengajar Universiti Putra Malaysia (HPUPM) from January 2022 until February 2023. Their clinico-demographic data were retrieved, and serum vitamin D and C-reactive protein (CRP) immunoassays were conducted. The vitamin D levels of each patient were categorized as normal (≥50 nmol/L) or low (<50 nmol/L). Statistical comparisons of the patients’ clinico-demographic parameters with vitamin D levels were conducted. Results: In univariable analysis of categorical variables, significantly higher proportion of female COVID-19 patients presented with low serum vitamin D levels compared with male COVID-19 patients (p=0.045; 85.3% vs 65.1%). Pertaining to continuous variables, younger COVID-19 patients demonstrated significantly higher prevalence of low vitamin D levels (p=0.040; 45.58 vs 54.90 years old). COVID-19 patients with lower CRP levels also demonstrated significantly higher proportion of low vitamin D levels (p=0.046; 35.70 vs 60.92 mg/dl). These three parameters (i.e. gender, age, and CRP levels) were included in the multivariable logistic regression analysis to determine which factor(s) remained significantly associated with low vitamin D levels. All three parameters did not show significance in the multivariable analysis. Conclusion: Absence of statistical significance in the multivariable analysis indicates that the individual associations between age, gender, and CRP levels with low vitamin D levels are not independent of each other. These suggest underlying interactions between these factors that influence their relationships with vitamin D levels, and further studies are required to clarify such interactions in COVID-19 patients.